Comparative Analysis of Carbon-Neutral District Heating Solutions Incorporating Waste Heat Recovery and Geothermal Exchange in Tropical Urban Settings - Rahardian Luthfi Prasetyo; Isra' Nuur Darmawan; Kholistianingsih (International Forum of Researchers and Lecturers, 2025)
This research investigates the potential of integrating waste heat recovery and geothermal exchange within district heating systems as a carbon-neutral energy solution tailored to tropical urban settings. Tropical climates present unique challenges for heating, ventilation, and air conditioning (HVAC) systems, including high humidity, temperature fluctuations, and increasing energy demands, particularly for cooling. This study aims to address these challenges by proposing a hybrid district heating system that combines renewable energy sources to improve energy efficiency and reduce carbon emissions. The methodology includes thermal and hydraulic modeling, performance simulation of the hybrid system under tropical climate conditions, and emission and energy efficiency analysis. The results indicate that the hybrid system significantly reduces energy consumption and carbon emissions compared to traditional heating systems, with waste heat recovery optimizing energy use and geothermal exchange enhancing system efficiency. The comparison with conventional systems and other environmentally friendly alternatives reveals that the hybrid system offers a cost-effective, sustainable solution for tropical urban areas. The study concludes that integrating waste heat recovery and geothermal exchange is feasible and can contribute to the creation of carbon-neutral cities. Future research should focus on optimizing geothermal systems in tropical climates and exploring further integration with other renewable energy sources to enhance system performance and sustainability.